The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1002/bmc.5140
|View full text |Cite
|
Sign up to set email alerts
|

Screening of hepatotoxic compounds in Psoralea corylifolia L., a traditional Chinese herbal and dietary supplement, using high‐resolution mass spectrometry and high‐content imaging

Abstract: Owing to the complexity of the composition of herbal and dietary supplements, it is a challenging problem to efficiently screen and identify active or toxic compounds. Psoralea corylifolia L. (PCL) was selected as the subbject to establish a methodology for rapid screening and identification of hepatotoxic compounds. High‐content imaging, ultra‐performance liquid chromatography and high‐resolution mass spectrometry were used in this study to detect the hepatotoxicity and identify unknown compounds in PCL sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
0
6
0
Order By: Relevance
“…It was reported that corylifolinin, at a mass fraction of 100 mg/L, could lead to an inhibition rate of approximately 60% in LO2 normal liver cells. Similarly (G. Z. Shi et al., 2021), established a strong correlation between corylifolinin and hepatotoxicity, suggesting the potential for liver damage. Another study (Z. Qin et al., 2021; Z. F. Qin et al., 2021) demonstrated that corylifolinin could inhibit human CYP and UGT enzymes, including CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP2E1, UGT1A1, UGT1A9, and UGT2B7.…”
Section: Toxicology and Safetymentioning
confidence: 78%
See 1 more Smart Citation
“…It was reported that corylifolinin, at a mass fraction of 100 mg/L, could lead to an inhibition rate of approximately 60% in LO2 normal liver cells. Similarly (G. Z. Shi et al., 2021), established a strong correlation between corylifolinin and hepatotoxicity, suggesting the potential for liver damage. Another study (Z. Qin et al., 2021; Z. F. Qin et al., 2021) demonstrated that corylifolinin could inhibit human CYP and UGT enzymes, including CYP2B6, CYP2C9, CYP2C19, CYP2D6, CYP2E1, UGT1A1, UGT1A9, and UGT2B7.…”
Section: Toxicology and Safetymentioning
confidence: 78%
“…Corylifolinin is a naturally occurring compound found in various plant species, with the highest concentrations residing in the seeds of P. corylifolia (Figure 2) (G. Z. Shi et al., 2021). P. corylifolia , often referred to as the “ageless herb,” is among the most utilized Chinese herbal medicines.…”
Section: Resourcesmentioning
confidence: 99%
“…Wang et al showed that when the mass fraction of IBC reached 100 mg/L, the inhibition rate of LO 2 normal liver cells could reach about 60% (Wang et al, 2020). Shi et al used spectral toxicity correlation analysis to study the effect of IBC on the ATP value of hepatocytes, taking the peak area of IBC as an independent variable, and obtained a correlation coefficient of 0.90542, indicating that IBC may have strong hepatotoxicity (Shi et al, 2021). Qin et al showed that IBC could inhibit human CYP and UGT enzymes.…”
Section: Toxicity Of Ibcmentioning
confidence: 99%
“…And recent studies have shown that IBC is expected to be used as an inhibitor of coronavirus due to its conjugated thick ring structure (Attia et al, 2020; Zhang et al, 2021). But at the same time, IBC also has certain toxicity, among which hepatotoxicity is more obvious (Shi et al, 2021). Existing reports at home and abroad mainly focus on pharmacological activity but lack a comprehensive review.…”
Section: Introductionmentioning
confidence: 99%
“…Apart from various pharmacological effects, Psoraleae Fructus is often used for medicinal diets with meat, walnut kernels, wine, or other foods. It is not only delicious but also a warm tonic that can improve immunity [ 3 , 4 ]. Scholars have extracted a variety of chemical components from Psoraleae Fructus , such as coumarins, flavonoids, and monoterpene phenols [ 5 ].…”
Section: Introductionmentioning
confidence: 99%